Performance of Moving Bed Biofilm Reactor Integrated Septic Tank in Treating Office Building Wastewater - Ahmad Soleh Setiyawan; Farisah Inarah Rahmat Hasby; Va Vandith; Prayatni Soewondo; Chihiro Yoshimura; Dyah Wulandari Putri (Journal of Engineering and Technological Sciences, 2023)
This research aimed to find the effect of initial concentration and hydraulic retention time (HRT) on modified septic tank (MST) performance in treating wastewater from an office building. The synthetic wastewater used had an average COD:TN:TP ratio of 84:28:1, adjusted to office building wastewater characteristics. The experiment was executed under steady conditions using three variations of HRT (12, 24, and 36 hours) and different initial concentrations of COD (106, 252 and 432 mg COD/L), TN (35, 85 and 146 mg N/L) and TP (1.26, 3 and 5.14 mg P/L). The result showed that the MST removed 82% to 92% of COD, 41% to 60% of TN, 45% to 61% of NH4, and 39% to 55% of TP. The maximum removal was achieved at 36 h of HRT, COD:TN (3:1), and COD:TP (84:1). One-way ANOVA showed that the initial concentration and HRT had significant effects on the performance of MST (p < 0.05). This suggests that appropriate control of the initial concentration and HRT in the MST can effectively remove organics and nutrients from office building wastewater.